Pengaruh Tunneling Incentive, Intangible Assets Dan Leverage Terhadap Transfer Pricing: (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Konsumen Primer Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Sevty Wahiddirani Saputri; Etis Kharisma (Yayasan Literasi Sains Indonesia, 2023)
This research is intended to know the impact of tunneling incentives, intangible assets, and leverage on transfer pricing partially and simultaneously. This research uses quantitative methods using secondary data types. This research uses manufacturing companies in the primary consumer goods sector listed on the Indonesian stock exchange in 2018-2022 as the research population. The number of samples obtained through purposive sampling technique was 14 companies from a total population of 103 companies with a research period of 5 consecutive years of observation so that the data used was 70 data. The tools used to test the data are regression analysis tests and panel data using Eviews version 9. The test stages that have been carried out prove that tunneling incentives have an effect on transfer pricing, intangible assets have an effect on transfer pricing, and leverage has an effect on transfer pricing. Meanwhile, tunneling incentives, intangible assets and leverage simultaneously influence transfer pricing. The coefficient of determination shows that the independent variable contributes 98.74% to transfer pricing, while the remaining 1.26% is influenced by other variables not included in this research